An Assessment of the Effects of Climate Change on Annual Streamflow in Rivers in Western Turkey - HISAR, Olcay (Inderscience Publishers, 2018)
Global warming and its impacts are known to cause serious problems in sustainability of natural resources. In this study, change-point analysis and trend analysis were applied to climatic (temperature, precipitation, evaporation) and streamflow data for Tuzla, Gediz and Buyuk Menderes rivers. Box-Jenkins technique and ARIMA model were used for trend analysis. Results showed that there were decreases in streamflow of all rivers. The paper suggests that climate change effects on streamflow could be changeable and that many factors (anthropogenic effects, geographical location, agricultural activities) should be considered. Management strategies specified regionally are required to mitigate the potential climate change effects.
Keywords: 13. Climate action; 15. Life on land; 6. Clean water